The modular structural system as an innovation for temporary public healthcare project of 4th-year architecture students at UIN Maulana Malik Ibrahim Malang - Bahar, Mohammad Arsyad; Samudro, Harida; Yulianto, Ahmad (Proceedings of the International Conference on Green Technology, 2021)
Abstract - The module structure system implements development by utilizing fabricated materials or components made outside the project site or on-site. Consumable shipping containers are often used to make architectural space rated more quickly and efficiently. The advantages of containers are customized, strength, durability, modular, labor, movable, availability, expense, and eco-friendly. The rapid spread of Covid-19 in various regions demands fast, proper, and adequate public health facilities. Containers can be an innovative solution for providing temporary, flexible, efficient, functional, and sustainable public health room facilities. This study describes the uses and advantages of modular container systems for architectural spaces. The result is a schematic design from the design studio of the 4th year architecture student of UIN Maulana Malik Ibrahim Malang, who is trying to improve the function of the use of consumable containers to get more benefits as a temporary architectural space for sustainability and public awareness of health and handling Covid-19.